FAKTOR-FAKTOR YANG MEMENGARUHI PURCHASE INTENTION LIVE STREAMING APLIKASI TIK TOK - Reswara, Hening Hasna; Wijaya, Nikodemus Hans Setiadi (Jurnal Ekonomi Dan Bisnis, 2024)
This study aims to examine the relationship of promotion among viral marketing, brand awareness, celebrity endorser, and affiliate marketing towards purchase intention on Tik Tok. It employed a purposive technique by distributing questionnaires through google form. In total, there were 145 respondents of millennials and Z generations who own Tik Tok. This study used the Statistical Package for Social Science (SPSS) 26 data analysist method. The data analysis resulted in the influence of viral marketing, celebrity endorser, brand awareness, and affiliate marketing on purchase intention with partial, simultaneous, and multiple linear regression tests. In addition, the test result proved that affiliate marketing has the strongest influence compare to other independent variables toward purchase intention with multiple linear regression value 0.695